The evolution of structure and properties for copolyamide fibers–containing benzimidazole units during the decomplexation of hydrogen chloride. (May 2016) - Li, Ke; Luo, Longbo; Huang, Jieyang; Ma, Xuhui; Wang, Huina; Feng, Yan; Liu, Xiangyang
A diamine monomer 2-(4-aminophenyl)-5-aminobenzimidazole (PABZ) was introduced to modify poly( p -phenylene terephthalamide) by copolymerization, and corresponding aromatic copolyamide fibers were prepared by wet spinning. Thermogravimetric analysis showed that the benzimidazole units of the as-spun copolyamide fibers can complex with hydrogen chloride (HCl) to form protonated benzimidazole units, and the decomplexation takes place above 280°C. It is interesting that the crystal orientation, crystallite size, and tensile strength increase significantly during the decomplexation. Fourier transform infrared spectroscopy proved that the decomplexation leads to the release of the electron donor C=N, which can form hydrogen bonding with NH in the PABZ unit. After removing HCl, the copolyamide fibers exhibit better planarity and stronger π–π conjugation between benzimidazole and benzene rings, which is conducive to the formation of π–π stacking. Thus, we suggest that the newly formed hydrogen bonding and the enhanced π–π stacking induce the closely packing and spontaneous orientation of the macromolecular chains, which lead to the sharp improvement of the tensile strength.